Malay for Malaya? Re-examining language debates in colonial Malaya from the 1920s–1940s - Tai, Cae Ryn (2019)
Scholars have often cited the establishment of a common vernacular language as the harbinger of nationalism in colonised countries. Resultantly, research on colonial Malaya has quoted Bahasa Melayu (Malay) as the logical choice of language for this developing nation. However, colonial Malaya was a multi-racial society. In much of current literature, scholars have thus chosen to study these racial groups in isolation, and in light of the respective colonial or vernacular sources. Consequently, and rather ironically, the perspectives of the educated class of Malayans is overlooked. Therefore, this paper aims to bring to the table the perspectives from the Malaya Tribune, a newspaper specifically catered to the English-speaking elite Asians of Malaya. The Tribune is a unique platform that speaks for these elites who shared a common colonial education while understanding and expressing the sentiments of their own respective vernacular communities. Therein lies its value. In examining this daily, contentions among the elite Malayans regarding language show that the simplistic association of Malay as logical for Malaya was actually much more complex. The discussions in the Tribune from the 1920s–1940s are thus a strong proponent of the supposition that current historical narratives are lacking in multidimensionality, ergo requiring re-examination.